2017
DOI: 10.1159/000481686
|View full text |Cite
|
Sign up to set email alerts
|

Is Colonoscopy Indicated in Young Patients with Hematochezia

Abstract: Background/Aims: While colonoscopy is indicated in patients >50 years old presenting with hematochezia, its role in those ≤50 remains debatable. This study aims to evaluate the role of colonoscopy in patients presenting with hematochezia who are ≤50 years old. Methods: A retrospective review of all patients aged ≤50 years who underwent colonoscopy for hematochezia in 2012 was conducted. Patient demographics, endoscopic details, and histological results were analyzed. Patients were stratified by age to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…and Koh et al ., who had significant findings in 11–15% of procedures. The specific incidence of CRC was greater in our study, with 1.9% of patients compared to <1% in these studies 19–22 . This is also greater than the age‐specific incidence of 31.6 per 100 000 (0.03%) in 40–49‐year‐olds, which reduces for each younger age group, identified by the AIHW 1 .…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…and Koh et al ., who had significant findings in 11–15% of procedures. The specific incidence of CRC was greater in our study, with 1.9% of patients compared to <1% in these studies 19–22 . This is also greater than the age‐specific incidence of 31.6 per 100 000 (0.03%) in 40–49‐year‐olds, which reduces for each younger age group, identified by the AIHW 1 .…”
Section: Discussioncontrasting
confidence: 56%
“…This is consistent with findings by Koh et al . and reinforces the importance of complete investigation with colonoscopy rather than flexible sigmoidoscopy 22 …”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Good et al provided a small study that seems to agree with our conclusions, 22 whereas earlier reports by Eckardt et al 30 and Carlo et al 31 found a very low risk of proximal neoplasia in similar groups of patients. Koh et al 32 found that within the group of patients younger than 50 years, patients in their 40s with outlet-type rectal bleeding were at a higher risk of colorectal neoplasia than those who were younger, making the case for colonoscopy, at least in this older subgroup. Muller et al 33 performed colonoscopies in 187 consecutive patients younger than 50 years who presented with outlet-type rectal bleeding.…”
Section: Discussionmentioning
confidence: 99%